"Peculiarities of Teaching Legal Disciplines in Universities at the Present Stage" - Vasilieva, I. G. (Problems of Engineer-Pedagogical Education, 2018)
The article considers the features of teaching legal disciplines in higher schools in modern times when the most important direction of reforms occurring in the country is connected with the formation of public confidence in the absolute value of law, in its universal character. The state should raise the legal consciousness of its citizens not only through the system of an effective mechanism of legal regulation and application of legal norms, but also through legal education. The purpose of vocational legal training of the future engineer-educator under the conditions of a higher educational institution is the formation of his/her professional and legal competence, that is the totality of professional and legal knowledge, skills, and readiness to perform all types of legal actions in engineering and pedagogical activity. The author notes that the teacher of legal disciplines should first of all teach each student to work with computer reference legal systems (GPS) – databases containing normative documents. The article emphasizes that in order to solve the problem of efficient acquisition of legal knowledge by students, the compulsory condition is the widest application of modern technologies in conjunction with interactive teaching technologies. The author considers the use of an interactive whiteboard, interactive lectures, such as "tête-à-tête lectures" or "press-conference lectures", and especially project methods, namely research, creative, gaming, informational and practice-oriented, as the most effective teaching technologies.